An evaluation tool for assessing performance in priority setting and resource allocation: multi-site application to identify strengths and weaknesses. (January 2016) - Hall, William; Smith, Neale; Mitton, Craig; Gibson, Jennifer; Bryan, Stirling
Introduction: An evaluation tool should help improve formal priority setting and resource allocation (PSRA) processes in Canada and elsewhere. These are crucial to maximizing value from limited resources. Methods: On the basis of case studies, balanced scorecard development protocols and use-focused evaluation principles, an evaluation tool was developed based on an existing framework for high PSRA performance and implemented in two health care organizations in British Columbia, Canada. Results: Implementation of the tool identified areas of strength, improvement and weakness in the pilot organizations' processes for PSRA including: communication, staff engagement and culture. Refinements were identified and incorporated into the tool for future application. Conclusion: This is the first documented multi-site application of such an evaluation tool. Broader dissemination should have use both in further refining the basis of the tool and in catalysing improved performance of PSRA practice.